A pena como arma: trabalho, intimidade e rotina nas cartas dos policiais paulistas (1870-1915) - Rosemberg, Andre (Centro de Pesquisa e Documentação de História Contemporânea do Brasil da Fundação Getúlio Vargas, 2016)
Abstract Through the analysis of letters written by policemen, we intend to shed light on little known aspects of the São Paulo Police in the beginning of the XX century. This very personal mode of communication allows us to catch a glimpse of the intimacy of policemen's lives, the presence of family, the porosity between both civil and institutional worlds. The epistolary form, so uncommon in a bureaucratic structure, uncovers the strategies of these workers in their daily relationship with the institution - the struggle for survival in a universe of poverty and hierarchical inequities; in short, a behind-the-scenes look into police work and routine.

Résumé Par l'analyse de lettres écrites par des policiers, nous avons l'intention de dévoiler des aspects peu connus de la police de São Paulo dans le contexte historique du tournant du XIXème siècle. La nature personnelle de cet instrument permet d'entrevoir des fragments de l'intimité des policiers, la présence de la famille, la porosité entre les mondes civil et institutionnel. Ces documents épistolaires, peu communs dans une structure bureaucratique, dévoilent les stratégies de ces travailleurs dans leur relation quotidienne avec l'institution - la lutte pour la survie dans un univers de pauvreté et d'iniquités hiérarchiques; enfin, les coulisses du travail et de la routine policière.

Resumo Por meio da análise das cartas escritas por policiais, pretendemos desvelar facetas pouco iluminadas da polícia de São Paulo no contexto histórico da virada do século XIX para o XX. Nas linhas desse instrumento tão pessoal, como são as cartas, vislumbram-se fragmentos da intimidade dos policiais, a presença da família, a porosidade entre os mundos civil e institucional. Desvelam-se na correspondência epistolar, pouco frequente numa estrutura burocrática, as estratégias desses trabalhadores na sua relação cotidiana com a instituição - o manejo pela sobrevivência num universo de pobreza e de iniquidades hierárquicas; enfim, as coxias do trabalho e da rotina policial.
The pen as a weapon: work, intimacy and routine in the letters of São Paulo's policemen (1870-1915)
Keywords: police; labour; police history; polícia; mundo do trabalho; história da polícia